A case series of melioidosis: An underdiagnosed entity in Kerala - Ebrahimkutty Shanimole Puthenpurayil; Pulikottil Shoba Kurian; Alexander Vipin Sam (Journal of Current Research in Scientific Medicine)
Melioidosis is an emerging infection in India and is caused by a Gram-negative oxidase-positive bacilli, Burkholderia pseudomallei which is present in soil and surface water in the endemic region. Clinical manifestations are protean varying from asymptomatic infection, multiple skin abscesses, chronic pneumonia mimicking tuberculosis, and fulminant septic shock with abscesses in multiple internal organs. Isolation of bacilli from aspirated fluids remains the gold standard of diagnosis. Lack of microbiological services in many parts of the state, protean nature of clinical manifestations, lack of awareness among clinicians, and misidentification of the organism as Pseudomonas spp leads to delay in diagnosis and treatment. We have, retrospectively, analyzed 14 cases with culture-proven melioidosis diagnosed during 10 years. Case records of culture-positive patients were retrospectively analyzed for demographic data, clinical characteristics, management, complications, and clinical outcomes. Out of these, 13 cases were male. The most common age group affected was 50–59 years. The major occupation affected was manual laborer. Nonbacteremic melioidosis accounted for 12 cases. Concerning clinical presentations, intra-abdominal abscesses mainly in the liver and spleen accounted for seven cases. All the isolates were susceptible to ceftazidime, meropenem, and doxycycline, whereas 12 isolates were susceptible to chloramphenicol, 11 isolates were susceptible to trimethoprim–sulfamethoxazole combination, and 10 cases were susceptible to amoxicillin–clavulanic acid and ciprofloxacin. Ten cases recovered with ceftazidime administration along with surgical drainage of abscess and three cases recovered with meropenem administration and surgical drainage. One patient expired and was on piperacillin–tazobactam. Melioidosis is a disease of public health importance and early clinical and laboratory diagnosis is crucial in the effective management of melioidosis.